The implementation of research and development policy in European and Asian countries - Janno Reiljan; Ingra Paltser (OrdnungsPolitisches Portal (OPO), 2013)
Research and development (R&D) policy has to fulfil a central role in innovation policy since it consists of government sector measures that support R&D in order to initialise and promote innovation. The authors of this article discuss first the theoretical reasoning for government sector intervention in R&D processes. The empirical study examines the level and structure of government sector resources and expenditures for R&D policy in EU member states (including Estonia), countries closely associated with the EU, China, Japan and South Korea. The aim of the article is to compare the position of these countries on the basis of R&D policy implementation from the aspect of resource and expenditure supply. In order to achieve the aim, the following research tasks are tackled: on the basis of research literature, the necessity, essence, measures and anticipated outcomes of R&D policy are explained to create the theoretical base for the empirical study; on the basis of the empirical analysis, an assessment on the international position of R&D policy implementation in several new EU member states and Asian countries is conducted. The data used in the empirical analysis is gathered from Eurostat and OECD databases.
Keywords: 330; market and system failures; R&D policy; EU; Estonia; South Korea